FRONTEND AND BACKEND DEVELOPER DIFFERENCE AND ADVANTAGES (Multidisciplinary Journal of Science and Technology, 2024)
Modern web application and site work exit in the process two main direction available : frontend and backend programming . Both direction to himself special tasks and requires technologies , however they are each other fills and strong cooperation through successful software product create for service does Frontend developer user who sees and which uses elements create with engaged , backend developer and server side , data base and of systems performance for is responsible . This frontend and backend developers in the article differences , advantages and their each one direction role seeing will be released